Presumed Deaths Among People Experiencing Street Homelessness in Chile: Analysis of Press-Reported Cases (2020–2025) in the Absence of Official Records - Estay, Felipe; Del Río, Alejandro (International Journal on Homelessness, 2026)
This descriptive paper presents deaths among people experiencing street homelessness in Chile, drawing from systematically and retrospectively compiled media reports from 2020 to August 2025. The findings reveal a disproportionately high burden of premature mortality, with violent and preventable causes - particularly homicide - dominating the causes. Other significant causes include accidents, illnesses, and hypothermia, underscoring diverse and persistent risks. The results highlight critical gaps in national data systems and the urgent need for targeted prevention strategies, including enhance safety, improved access to healthcare, seasonal risk mitigation, and comprehensive housing interventions. Establishing standardized real-time mortality monitoring could enable earlier risk detection and more effective evidence-based policies to reduce preventable deaths and protect the rights and dignity of this marginalized population.